Principal Influence: A Catalyst for Positive School Climate - Smith, Page A.; Escobedo, Patty; Kearney, Wowek Sean (International Journal of Education Policy and Leadership, 2020)
This investigation explores the relationships between principal influence and four facets of organizational climate: institutional vulnerability, collegial leadership, achievement press, and professional teacher behavior. Data were collected from 2,033 teachers at 112 elementary schools in two states from the Southern and Midwestern United States. The results of multiple linear regression analyses show that the independent variables of principal influence, SES, and school size combined to form a significant portion of the variance in organizational climate. The four facets of organizational climate explored in this study provide insight into specific mechanisms through which influential principals can positively affect schools.